Climate Adaptive Technology In Maintaining Vernacularism Of Urban Kampong Case study: KampungAdat (Indiginous) Mahmud, Bandung District,West Java - Marcus Gartiwa (Bandar Lampung University (UBL), 2013)
Vernacular architecture has been developed to fulfill human need and toÂ encourage their live, which make architecture has close relationship with humanÂ culture(Rapoport, 1969). These process make vernacular building has a uniqueness, suchÂ as :a) non-engineered construction in response to the needs of their occupants, b) StruggleÂ with their physical environment, c) it cannot be separated from locality, d) ecologicalÂ wisdom. Such holistic approach promotes architecture should have paradigms : 1) buildingsÂ which physically last long, require little maintenance, and save in energy, 2) the wayÂ architecture and environment ought to be in fostering manâs spirit. Kampung AdatÂ (indigenous) Mahmud as urban kampong has implemented climate-adaptive technology inÂ sustaining the built enviroment which such vernacular wisdom. The aim of the research isÂ to get better understanding how community of the Kampong could do climate-adaptiveÂ technology, which includes : 1) to identify and to evaluate climate challenge, 3) to analyseÂ technology as adaptation to climate, 4) to evaluate the effectiveness each technology, 5) toÂ develop the potential of climate adaptive technology. The methodology of research isÂ qualiative descriptive, which based on observation and actual measurement. The useful ofÂ the research is: 1) to get better understanding of local technology in adapting to climate,Â 2)to develop such adaptive technology. Such principles must be applied in : 1) HouseÂ Shape which can better minimize or withstand the impact of natural disaster, 2) BuildingÂ method; sustainable construction practices are low cost, practical and environmentallyÂ appropriate, 3)Building Components, 4)Building Materials,which are either made fromnaturally available sources or from organic raw materials.